Newborn Blood Spot Screening for Sickle Cell Disease by Using Tandem Mass Spectrometry: Implementation of a Protocol to Identify Only the Disease States of Sickle Cell Disease. (1st February 2014) - Moat, Stuart J; Rees, Derek; King, Lawrence; Ifederu, Adeboye; Harvey, Katie; Hall, Kate; Lloyd, Geoff; Morrell, Christine; Hillier, Sharon
Abstract: BACKGROUND: The currently recommended technologies of HPLC and isoelectric focusing for newborn blood spot screening for sickle cell disease (SCD) identify both the disease and carrier states, resulting in large numbers of infants being followed up unnecessarily. Analysis of blood spot tryptic peptides performed by using tandem mass spectrometry (MS/MS) is an alternative technology to detect hemoglobin (Hb) variant disorders. METHODS: We analyzed 2154 residual newborn blood spots and 675 newborn blood spots from infants with Hb variants by using MS/MS after trypsin digestion. Screening cutoffs were developed by using the ratio between the variant peptide–to–wild-type peptide abundance for HbS, C, D Punjab, O Arab, Lepore, and E peptides. A postanalytical data analysis protocol was developed using these cutoffs to detect only the disease states of SCD and not to identify carrier states. A parallel study of 13 249 newborn blood spots from a high-prevalence SCD area were analyzed by both MS/MS and HPLC. RESULTS: Screening cutoffs developed distinguished the infants with the disease states of SCD, infants who were carriers of SCD, and infants with normal Hb. In the parallel study no false-negative results were identified, and all clinically relevant cases were correctly identified using the MS/MS protocol. Unblinding the data revealed a total of 328 carrier infants that were successfully excluded by the protocol. CONCLUSIONS: The screening protocol developed correctly identified infants with the disease states of SCD. Furthermore, large numbers of sickle cell carrier infants were successfully not identified, thereby avoiding unnecessary follow-up testing and referral for genetic counseling.